Incidence of tuberculosis and its predictors among under-five children with severe acute malnutrition in North Shoa, Amhara region, Ethiopia: a retrospective follow-up study - Aynalem, Yared Asmare; Getacher, Lemma; Ashene, Yonatan Eshete; Yirga Akalu, Tadesse; Yideg Yitbarek, Getachew; Yeshanew Ayele, Fanos; Aklilu, Dawit; Marfo, Emmanuel Akwasi; Alene, Tamiru; Shibabaw Shiferaw, Wondimeneh (Frontiers in Pediatrics, 2023)
Although tuberculosis (TB) is one of the significant public health challenges in severely malnourished children throughout the globe, it is a severe issue for countries such as Ethiopia, with significant resource limitations. Few studies have examined the incidence of tuberculosis and its predictors among children under five years of age with severe acute malnutrition in developing countries, and there is a paucity of data. This study aimed to estimate the incidence of tuberculosis and its predictors among under-five children with severe acute malnutrition (SAM) in North Shoa, Amhara region, Ethiopia. Methods: An institution-based retrospective follow-up study was conducted between January 20, 2014, and June 20, 2019. The sample size was calculated using STATA, which yields a total of 345 charts that were selected with systematic random sampling. Data entry was performed using Epi-data version 4.2 and analyzed with STATA 14. Kaplan-Meier survival curves were computed. Cox proportional hazard models were fitted to detect the determinants of tuberculosis. The hazard ratio with a 95% confidence interval was subsequently calculated. Variables with p-values < 0.05 were considered statistically significant. Results: The incidence rate of tuberculosis among children under five years of age with SAM was 4.6 per 100 child months (95% CI: 7.29, 8.9). Predictors of TB were history of contact with known TB cases [AHR: 1.68 (95% CI: 1.11,3.12)], HIV/AIDS [AHR: 3.41 (95% CI: 1.10, 11.191)], diarrhea [AHR: 1.3 (1.07 (1.59)], pneumonia [AHR: 2.10 (1.76,12)], not supplying zinc [AHR: 2.81 (1.054, 4.19)], and failed appetite taste [AHR: 2.3 (1.76, 3.52)]. Conclusions: In this study, the incidence rate of TB was high. Diarrhea, not supplying zinc, failed appetite taste, history of contact with known TB cases, HIV/AIDS, and pneumonia were significant predictors of TB.Keywords: children; severe malnutrition; tuberculosis; Ethiopia